Public Continuum Beliefs for Different Levels of Depression Severity - Makowski, Anna C.; Schomerus, Georg; von dem Knesebeck, Olaf (Frontiers in Psychiatry, 2021)
Introduction: The notion that depression is a disorder that moves along a continuum is well established. Similarly, the belief in the continuity of mental illness is considered an important element in the stigma process. Against this background, it is the aim of this study to examine whether public continuum beliefs vary with the severity of depressive symptoms. Methods: Analyses were based on computer-assisted telephone interviews (CATI) conducted in winter 2019/2020 in Germany (N=1,009, response rate 46.8%). Using three vignettes representing mild, moderate, and severe depressive symptoms, beliefs regarding the continuity of symptoms respectively a fundamental difference were assessed with seven items. Sociodemographic characteristics and own experiences with depression (affliction and contact) were introduced as covariates. Results: Significant differences between the three groups of severity were found for the majority of the items measuring continuum beliefs or perceived fundamental difference. However, only few items showed a linear trend indicating a parallel between symptom severity and beliefs. Multivariate regression models showed that a moderate degree of depression was positively associated with stronger continuum beliefs but also with greater perceived difference compared to the mild degree, while no significant associations emerged for the severe vignette. Limitations: Although a comparison of our sample with official statistics supports the external validity, we cannot rule a selection bias. It is arguable in how far short case vignettes convey a holistic picture of a person affected by depressive symptoms. Conclusion: Our results do not indicate a parallel between symptom severity and public continuum beliefs.